K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(x^n+x^{n+3}-x^n=x^{n+3}=x^n\cdot x^3\)

31 tháng 8 2021

\(x^{n+3}+x^n=x^n.x^3+x^n=x^n\left(x^3+1\right)=x^n\left(x+1\right)\left(x^2-x+1\right)\)

31 tháng 8 2021

\(x^{n+3}+x^n=x^n\left(x^3+1\right)=x^n\left(x+1\right)\left(x^2-x+1\right)\)

22 tháng 2 2018

30 tháng 12 2022

\(5\left(3x^{n+1}-y^{n-1}\right)-3\left(x^{n+1}+2y^{n-1}\right)+4\left(-x^{n+1}+2y^{n-1}\right)\)

\(=15x^{n+1}-5y^{n-1}-3x^{n+1}-6y^{n-1}-4x^{n+1}+8y^{n-1}\)

\(=8x^{n+1}-3y^{n-1}\)

27 tháng 6 2019

xn - 1(x + y) - y(xn - 1 + yn - 1)

= xn - x + y - yxn - y2 n - 1

25 tháng 12 2018

x(x – y) + y(x – y)

= x.x – x.y + y.x – y.y

= x2 – xy + xy – y2

= x2 – y2 + (xy – xy)

= x2 – y2

23 tháng 8 2018

kho that

a: ta có: \(x\left(x-y\right)+y\left(x-y\right)\)

\(=\left(x-y\right)\left(x+y\right)\)

\(=x^2-y^2\)

b: Ta có: \(x^{n-1}\left(x+y\right)-y\left(x^{n-1}+y^{n-1}\right)\)

\(=x^n+x^{n-1}\cdot y-x^{n-1}\cdot y-y^n\)

\(=x^n-y^n\)

6 tháng 9 2017

\(x^{n-1}\left(x+y\right)-y\left(x^{n-1}+y^{n-1}\right)\)

=\(x^n+x^{n-1}y-x^{n-1}y-y^n\)

=\(x^n-y^n\)

6 tháng 9 2017

\(x\left(x-y\right)+y\left(x-y\right)\)

\(=x.x-x.y+y.x-y.y\)

\(=x^2-xy+yx-y^2\)

=\(x^2-y^2\)

3 tháng 4 2018

a) x(x – y) + y(x – y) = x2 – xy + yx – y2 = x2 – xy + xy – y2 = x2 – y2

b) xn–1(x + y) – y( xn–1 + yn–1 ) = xn + xn–1y – yxn–1 – yn

= xn + xn–1y – xn–1y – yn = xn - yn

a) x (x - y) + y (x - y) = x2 – xy+ yx – y2

                                = x2 – xy+ xy – y2

                                = x2 – y2

b) xn – 1 (x + y) – y(xn – 1 + yn – 1) =xn+ xn – 1y – yxn – 1 - yn

                                                    = xn + xn – 1y - xn – 1y - yn

                                                    = xn – yn.

25 tháng 10 2021

a. x4 : xn = x4 - n

b. xn : x5 = xn - 5

c. \(\left(3x^4y^3+\dfrac{1}{2}x^3y^2+x^5y\right):4x^ny^n\)

\(3x^4y^3:4x^ny^n+\dfrac{1}{2}x^3y^2:4x^ny^n+x^5y:4x^ny^n\)

\(\dfrac{3}{4}x^{4-n}y^{3-n}+\dfrac{1}{8}x^{3-n}y^{2-n}+\dfrac{1}{4}x^{5-n}y^{1-n}\)

25 tháng 10 2021

a: \(x^4:x^n=x^{4-n}\)

b: \(x^n:x^5=x^{n-5}\)